Vitamin E and Selenium Reduce Prednisolone Side Effects in Rat Hearts - Bardas, Ebru; Arslan, Yusuf Kemal; Polat, Seher; Erisir, Mine; Uslu, Gozde Atila; Cetin, Nihal; Cicek, Betul (Imr Press, 2020)
Aim of this work was to determine the effects of dietary intake vitamin E and Se on lipid peroxidation (LPO) as Thiobarbituric acid reactive substances (TBARS) and on the antioxidative defense mechanisms in heart tissues of rats treated with high doses of prednisolone. 250 adult male Wistar rats were randomly divided into 5 groups and fed with normal diet. Additionally groups 3, 4, and 5 received a daily supplement in their drinking water of 20 mg vitamin E, 0.3 mg Se, and a combination of vitamin E and Se (20 mg/0.3 mg), respectively, for 30 days. For 3 d subsequently, control group was treated with placebo, and remaining four groups were injected intramuscularly with 100 mg/kg prednisolone. After last administration of prednisolone, 10 rats from each group were killed at 4, 8, 12, 24, and 48 h and the activities of antioxidant enzymes and the levels of GSH and TBARS were measured. GSH-Px, CAT activities and GSH levels decreased starting from 4th hour to 48% and 65% of control levels by 24th hour, respectively and it reincreased to control levels at 48th hour in the prednisolone group (p < 0.001, p < 0.001). In addition, prednisolone administration led 2-fold increase in heart TBARS levels at 24th hour (p < 0.001). E vitamins and Se inhibited the increase in heart TBARS and the decrease in antioxidative enzymes levels. Therefore, It is concluded that vitamin E and Se may have a preventive role in decreasing the increase of TBARS caused by prednisolone administration in our study.
Keywords: Prednisolone; selenium; vitamin E; heart; oxidative stress; antioxidant defense